Clinical Outcomes of Integrated Treatment strategies in Progressive Familial Intrahepatic Cholestasis: Single Center Experience - Ahmed, Hafiz Bilal; Abbas, Syed Hasnain; Bashir, Hafiz Aamir; Rizvi, Muhammad Usman Ali; Hassan, Syed Waqas; Umar , Muhammad (Pakistan Armed Forces Medical Journal, 2026)
B Objective: To evaluate the effectiveness of integrated treatment modalities based on outcomes and survival. Study Design: Progressive Longitudinal. Place and Duration of Study: Pir Abdul Qadir Shah Jeelani Institute of Medical Sciences (PAQSJIMS), Gambat, Pakistan, from Jan 2019 to Dec 2023. Methodology: This study enrolled 43 patients with Progressive Familial Intrahepatic Cholestasis (PFIC), who were categorized into three treatment groups: medical management (n=22), Partial Internal Biliary Diversion (PIBD) (n=9), and Living Donor Liver Transplantation (LDLT) (n=12). Outcomes were assessed using pruritis scores, survival rates, and morbidity using Calvin-Dindo classification. Results: In the medical management group, mean follow-up was 39.14±20.49 months, with a 90.90% survival rate and significant pruritis improvement (2.09±1.01, p=0.006) while the PIBD group had a mean follow-up of 49.89±21.07 months, a 100% survival rate, and significant pruritis reduction (0.78±0.83, p=0.021) but the LDLT group had a mean follow-up of 24.42±12.42 months, a 91.66% survival rate, and major morbidity (III-b). Overall survival across groups was 68.61±2.44 months. Conclusion: Medical management and PIBD could be considered as initial treatments for well-compensated PFIC patients, while liver transplant is recommended only for cases with treatment failure.